Jurisprudential Examination of the Constituent Kernels of Fair Hearing - Ojumu, Cletus; Emeje, Aruwa; Nwajah, Patrick Okereke (ABUAD Law Journal, 2022)
The importance of fair hearing in the administration of justice can never be underestimated in the existence of mankind. Fair hearing is ordained by God and that is why God gave Adam and Eve the opportunity of being heard before giving them punishment, ditto to Cain. The right to fair hearing requires that an individual shall not be penalised by a decision affecting his rights or legitimate expectations unless he has been given prior notice of the case against him, a fair opportunity to answer it and the opportunity to present his own case against. It also requires that the person hearing the matter be an unbiased person and should not have a likelihood of bias. It is founded on the twin pillars of justice expressed in Latin maxim Audi alteram partem and Nemo judex in causa sua. This article examines the principles of fair hearing andits constituent elements in our adversarial jurisprudence. It achieves this through doctrinal method of research using primary sources; Constitution,statutes,conventionsand case laws and secondary sources materials; books, journal articles and online materials as the methodology of this research.The paper finds that in every adjudicatory proceedings, all parties must be placed on an equal platform and given an opportunity to testify before a balanced and an impartial judge acceptable to all as fair and just. The paper recommends that Judges and those sitting over disputes must ensure fair hearing principles is observed and eschew bias or likelihood of bias or sentiments which will put a stumbling block to the adjudicatory wheel of fair trial.